CHILEAN LICHEN AND MOSSES MODIFIED CARBON PASTE ELECTRODES FOR MONITORING DISSOLVED ECOTOXIC METAL IONS - Lara Henriquez, Nelson Agustín; Hernandez-Saravia, Lucas Patricio; Orellana, Sandra; Ogalde, Juan Pablo (Journal of the Chilean Chemical Society, 2025)
Lichens (a symbiotic association of fungi and algae) and mosses are capable of accumulating heavy metals in their tissues. The retention of ecotoxic metals may take place in the functional groups that contain oxygen and nitrogen atoms, most likely carboxylic groups that form part of the cell wall of the fungus, through an ion exchange process. In this work, the study of carbon-lichen paste electrodes and carbon-moss paste electrodes has been carried out. Eighteen species of lichens and two species of mosses were used as sensitive agents. Additionally, the response of each of them with nine metal ions such as Cu, As, Pb, Hg, Zn, Cd, Al, Mo and Cr was studied. Being the electrode that is most sensitive to the lichen Protousnea Magallánica and the mosses Hypnum Cupresiforme and Ortotrichum Assimile, it presents better signals with the lead (II), Copper (II) and Mercury (II) ion.